Kondisi Kualitas Perairan untuk Mendukung Budidaya Lobster di Kabupaten Lombok Utara, Provinsi Nusa Tenggara Barat - Muhammad Junaidi; Nurliah Nurliah; Fariq Azhar (LPPM Universitas Mataram, 2018)
Lobster (Spiny lobster, Panulirus sp) is an important economic value commodity, then it needs to be developed through cultivation. North Lombok Regency has potential coastal and coastal resources for the development of marine aquaculture. Therefore, this study was to determine the condition of water quality in North Lombok Regency, West Nusa Tenggara Province to support the development of lobster aquculture. Water quality data collection was carried out in May 2018. A total of 23 stations that were spread out in simple random locations were collected at the research location.Water quality parameters collected include: temperature, salinity, pH, dissolved oxygen (DO), brightness, turbidity, nitrate (NO3-N), phosphate (PO4-P) and plankton.The results showed that the water conditions of North Lombok Regency still meet the range of quality standards or values recommended for lobster cultivation. Based on analysis of the statistics multivariate used in this research divide research locations into three different regions , the waters of the south (Gulf Sire) , middle parts in Tanjung and Gangga District, and the northern in off shore.The result of this research is expected to be able as additional information to support the development of the cultivation of spiny lobster in North Lombok Regency